Delayed re-laparotomy after total hysterectomy - Bhatnagar, Paridhi; Desai, Erika; Patel, Uday; Leuva, Bakul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Since beginning it’s a dilemma whether to remove or preserve the ovaries. In the present study an attempt is made to understand this phenomenon and to have some direction for removal of ovaries. Preservation of the ovaries at the time of hysterectomy does not seem to compromise patient care. Impaired function or failure of the retained ovaries, however, is not uncommon; close post-treatment surveillance is therefore important in terms not only of recurrent disease but of function of the ovaries as well. Methods: This study was done on 37 patients in duration of 3 years from June 2009 to May 2012. It is a retrospective statistical hospital based study of re-laparotomy done in post hysterectomised patients. Results: The most common pathology in these patients was a simple ovarian cyst (45.95%), followed by endometriotic cyst (21.62%), mucinous adenoma (8.10%), serous cyst adenoma (5.40%), serous cyst adenocarcinoma (2.70%) and poorly differentiated adenocarcinoma (2.70%). Conclusions: Emergence of pelvic mass after hysterectomy poses diagnostic and therapeutic challenge to gynecologists. In future, as the patients become more aware and the clinicians more enlightened on the long term benefits and risks of hormone replacement therapy, decisions might be easier for the patients and the clinicians alike.